Differential Requirements for the RAD51 Paralogs in Genome Repair and Maintenance in Human Cells - Garcin, Edwige B.; Gon, Stéphanie; Sullivan, Meghan R.; Brunette, Gregory J.; Cian, Anne De; Concordet, Jean-Paul; Giovannangeli, Carine; Dirks, Wilhelm G.; Eberth, Sonja; Bernstein, Kara A.; Prakash, Rohit; Jasin, Maria; et al. (PLoS genetics, 2019)
Deficiency in several of the classical human RAD51 paralogs [RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3] is associated with cancer predisposition and Fanconi anemia. To investigate their functions, isogenic disruption mutants for each were generated in non-transformed MCF10A mammary epithelial cells and in transformed U2OS and HEK293 cells. In U2OS and HEK293 cells, viable ablated clones were readily isolated for each RAD51 paralog; in contrast, with the exception of RAD51B, RAD51 paralogs are cell-essential in MCF10A cells. Underlining their importance for genomic stability, mutant cell lines display variable growth defects, impaired sister chromatid recombination, reduced levels of stable RAD51 nuclear foci, and hyper-sensitivity to mitomycin C and olaparib, with the weakest phenotypes observed in RAD51B-deficient cells. Altogether these observations underscore the contributions of RAD51 paralogs in diverse DNA repair processes, and demonstrate essential differences in different cell types. Finally, this study will provide useful reagents to analyze patient-derived mutations and to investigate mechanisms of chemotherapeutic resistance deployed by cancers.